2015
DOI: 10.1038/srep13513
|View full text |Cite
|
Sign up to set email alerts
|

A Rich-Club Organization in Brain Ischemia Protein Interaction Network

Abstract: Ischemic stroke involves multiple pathophysiological mechanisms with complex interactions. Efforts to decipher those mechanisms and understand the evolution of cerebral injury is key for developing successful interventions. In an innovative approach, we use literature mining, natural language processing and systems biology tools to construct, annotate and curate a brain ischemia interactome. The curated interactome includes proteins that are deregulated after cerebral ischemia in human and experimental stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We also observed that this prediction performance was significantly stronger in Women compared to Men (r = 0.29 in Women and r = − 0.03 in Men of Sample 1 ). Again, a possible cause might be the involvement of ovarian hormones, targeting specifically the most densely interconnected hub structures of the connectome (Alawieh et al 2015) as well as influencing level of Extraversion (Jokela et al 2009; Ziomkiewicz et al 2012). However, more studies are needed to prove this interaction between Extraversion, estrogen, and the topographical properties of whole-brain functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that this prediction performance was significantly stronger in Women compared to Men (r = 0.29 in Women and r = − 0.03 in Men of Sample 1 ). Again, a possible cause might be the involvement of ovarian hormones, targeting specifically the most densely interconnected hub structures of the connectome (Alawieh et al 2015) as well as influencing level of Extraversion (Jokela et al 2009; Ziomkiewicz et al 2012). However, more studies are needed to prove this interaction between Extraversion, estrogen, and the topographical properties of whole-brain functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…When a PPI network related to a disease exhibits a rich-club formation, it evinces the existence of a pathological powerhouse within the network, composed of the most influential components which have to their credit of providing the network robustness and stability ( Alawieh et al, 2015 ). We evaluated the existence of a rich-club structural ordering in the SB network using brainGraph package in R and the network was found to exhibit a rich club structural ordering as indicated by an increasing rich-club coefficient ϕ( k ) as k increased ( Figure 8A ).…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the properties of the constructed PKCζ interactome network, a rich-club analysis was conducted. A rich club is a set of high-degree nodes that are more densely interconnected than predicted by the node degrees alone [ 29 ]. The rich-club nodes may form a hub that is used by the other components in the network to influence each other.…”
Section: Resultsmentioning
confidence: 99%
“…The power-law degree distributions and adjacency matrices of the networks were generated using MATLAB. The rich-club coefficient is computed as described by others [ 28 , 29 ]. Briefly, we generated 1000 comparable random networks with equal size and the same degree distribution by rewiring to calculate the normalized rich-club coefficient.…”
Section: Methodsmentioning
confidence: 99%